The impact of traumatic childbirth on women: scoping review - Nogueira, Jesuína; Faria , Alexandra; Filipe , Filipa; Sousa , Ana Paula; Tavares , Márcio (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: Satisfaction with childbirth is related to how it’s experienced by the woman. Traumatic childbirth can lead to a series of negative outcomes with implications for women's mental health. Objective: To map the available evidence on women's perceptions of the impact and consequences of a traumatic birth experience. Methods: A scoping review was conducted following the guidelines of The Joanna Briggs Institute. Results: Nine articles published between 2019 and 2023 were included, employing both qualitative and quantitative approaches, identifying factors considered by women as traumatic during childbirth, including: obstetric practices, factors related to support, and factors related to the healthcare professionals. Conclusion: Recognizing the complexity of traumatic childbirth and its influencing factors, such as previous experiences, support during childbirth, communication with health professionals, and unexpected events, is essential. Knowing these factors makes it possible to alert health professionals to the importance of adopting more humanized practices that prevent women from having negative experiences and, consequently, guarantee them a positive childbirth experience.